Novel DSP Spectrin 6 Region Variant Causes Neonatal Erythroderma, Failure to Thrive, Severe Herpes Simplex Infections and Brain Lesions - Svetlana Vakkilainen; Laura Puhakka; Paula Klemetti; Kaarina Heiskanen; Mikko Seppänen; Mikko Muona; Celine Posseme; Darragh Duffy; Timo Väisänen; Outi Elomaa; Maarit Palomäki; Harri Saxén; et al. (Medical Journals Sweden, 2019)
Desmoplakin (DSP) and Desmoglein 1 (DSG1) variants result in skin barrier defects leading to erythroderma, palmoplantar keratoderma and variable [AQ4] other features. Some DSG1 variant carriers present with SAM syndrome (Severe dermatitis, multiple Allergies, Metabolic wasting) and a SAM-like phenotype has been reported in 4 subjects with different heterozygous DSP variants. We report here a patient with a novel DSP spectrin region (SR) 6 variant c.1756C>T, p.(His586Tyr), novel features of brain lesions and severe recurrent mucocutaneous herpes simplex virus infections, with a favourable response to ustekinumab. Through a review of reported cases of heterozygous variants in DSP SR6 (n = 15) and homozygous or compound heterozygous variants in DSG1 (n = 12) and SAM-like phenotype, we highlight phenotypic variability. Woolly hair, nail abnormalities and cardiomyopathy characterize patients with DSP variants, while elevated immunoglobulin E and food allergies are frequent in patients with DSG1 variants. Clinicians should be aware of the diverse manifestations of desmosomopathies.